Cationic starch: Safe and economic harvesting flocculant for microalgal biomass and inhibiting E. coli growth - El-Naggar, Mehrez E.; Samhan, Farag A.; Salama, Abeer A.A.; Hamdy, Rehab M.; Ali, Gamila H. (International journal of biological macromolecules, 2018)
Cationized starch-based flocculation processes are the subject of increasing attention because of their non-toxicity, biodegradability and relatively low price synthesized. The study aimed to evaluate the flocculability of different cationic starches using different concentrations of glycidyltrimethylammonium chloride (GTAC) with different degree of substitution (DS) ranged from 0.13 to 0.57. Cationized starch were characterized using Fourier Transform Infrared (FTIR), scanning electron microscopy (SEM) and toxicity checked using experimental animal procedure. They were used in comparison with aluminum sulphate for harvesting microalgal biomass collected from high rate algal pond (HRAP) at Zenin wastewater treatment plant (WWTP), Giza, Egypt. Jar test showed that gradual increase of aluminum sulphate doses (50–400 mg/L) has reduced algal suspension consequently turbidity with accompanied pH decrease from 8.6 to 6.6. Cationic starch with low DS has shown efficiency as flocculants by reducing turbidity of algal suspension from 110 to ≈2 NTU by gradual increase from 10 to 60 mg/L without change in pH value. Fecal coliforms and E. coli were inhibited from 9.6 × 102 and 8.4 × 10 CFU/ml to non-detectable count. Cationic starch with high DS (0.57) has the least effect of algae harvesting and turbidity reduction that 40 NTU after increase the dose to 60 mg/L. Results showed that 10 mg of cationic starch (DS = 0.13) has achieved the same flocculation efficiency of 100 mg of aluminum sulphate. In conclusion, further investigation is required to increase the degree of substitution of cationic starch, consequently the flocculation efficiency might be improved. •Cationized starch-based flocculation with different DS was prepared.•Fecal coliforms and E. coli were inhibited from 9.6 × 102 and 8.4 × 10 CFU/ml to non-detectable count.•Cationic starch (10 mg) has achieved the same flocculation efficiency of aluminum sulphate (100 mg).